2012
DOI: 10.1159/000341988
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Myocardial Infarction with Sudden Sensorineural Hearing Loss: A Population-Based Case-Control Study

Abstract: Objective: Although the etiology of sudden sensorineural hearing loss (SSNHL) remains unknown, there is increasing evidence suggesting an underlying cardiovascular pathomechanism. This study set out to explore a possible association between acute myocardial infarction (AMI) and having previously been diagnosed with SSNHL by using a population-based dataset with a case-control design. Methods: In this study, we utilized administrative claims data from the Taiwan National Health Insurance program to identify 48,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 50 publications
2
36
1
Order By: Relevance
“…As noted, SSNHL is comorbid with many disorders like cardiovascular and cerebrovascular events. 12,47 Even though all dates of IDA diagnosis in the present study were prior to the SSNHL diagnosis, which rendered an IDA diagnosis irrelevant to various examinations following the SSNHL event, it was still possible that the SSNHL population received laboratory tests more frequently than the control group because of other comorbid diseases. Nonetheless, this potential bias would have little effect on the conclusions.…”
Section: Discussionmentioning
confidence: 84%
“…As noted, SSNHL is comorbid with many disorders like cardiovascular and cerebrovascular events. 12,47 Even though all dates of IDA diagnosis in the present study were prior to the SSNHL diagnosis, which rendered an IDA diagnosis irrelevant to various examinations following the SSNHL event, it was still possible that the SSNHL population received laboratory tests more frequently than the control group because of other comorbid diseases. Nonetheless, this potential bias would have little effect on the conclusions.…”
Section: Discussionmentioning
confidence: 84%
“…We found that the prevalence of hyperlipidemia, diabetes mellitus, and hypertension was higher among patients with SSNHL, a result consistent with the findings reported in previous studies. [26][27][28]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to problems in arterial circulation that directly supplies the organ, systemic ischemia, such as that caused by atherosclerosis and hypertension, has been evaluated for an association with SSNHL 4 , 5 . Several previous studies have demonstrated the risk of MI in SSNHL subjects 6 , 7 . A population-based case-control study reported an odds ratio of 1.55 for a history of SSNHL in acute myocardial infarction (AMI) subjects (95% confidence interval [95% CI] = 1.30–1.70, P < 0.001) 7 .…”
Section: Introductionmentioning
confidence: 94%
“…Several previous studies have demonstrated the risk of MI in SSNHL subjects 6 , 7 . A population-based case-control study reported an odds ratio of 1.55 for a history of SSNHL in acute myocardial infarction (AMI) subjects (95% confidence interval [95% CI] = 1.30–1.70, P < 0.001) 7 . Based on age groups, 50–64- and ≥65-year-old groups with SSNHL demonstrated adjusted hazard ratios (HRs) of 1.62 and 1.28 for MI, respectively (P = 0.0064 and P < 0.001, respectively) 6 .…”
Section: Introductionmentioning
confidence: 94%